Survive the night : a novel - Sager, Riley ([New York] : Dutton, Penguin Random House LLC, 2021)
"It's November 1991. George H. W. Bush is in the White House, Nirvana's in the tape deck, and movie-obsessed college student Charlie Jordan is in a car with a man who might be a serial killer..."--
Keywords: Serial murderers -- Fiction; College students -- Fiction; Children and strangers -- Fiction; Thrillers (Fiction)